Painted Landscapes: Territory, Roads and Settlements of Apulia et Calabria on the Tabula Peutingeriana - Piepoli, Luciano (Eikón / Imago, 2020)
The article examines images of roads, settlements and landscapes of Apulia et Calabria depicted on segments V,2-5 and VI,1-2 of the Tabula Peutingeriana, a picta road map drawn up between the middle and the end of the 4 th century. Apulia et Calabria – a regio established by Augustus and transformed into a provincia at the end of the 3 th century – developed on a territory almost corresponding to today’s Puglia (southern Italy). The iconographic repertoire has been analyzed in the light of the historical, archaeological and epigraphic known documentation about the Roman administrative unit and in the light of the previous general studies focused on the stylistic peculiarities and interpretation of the images depicted on the Tabula.